Correction: A shock tube study of the branching ratios of propene + OH reaction. Issue 37 (27th August 2015) - Badra, Jihad; Khaled, Fethi; Giri, Binod Raj; Farooq, Aamir
Abstract : Correction for 'A shock tube study of the branching ratios of propene + OH reaction' by Jihad Badra et al., Phys. Chem. Chem. Phys., 2015, 17, 2421–2431.